Environmental impact and drainage geochemistry in the vicinity of the Harput Pb-Zn-Cu veins, Elazi?, SE Turkey - Kalender, Leyla; Bölücek, Cemal (My University, 2007)
The aim of this study was to examine the environmental impact of major, minor and rare-earth elements (REE) in spring waters and major and minor elements in stream sediments proximal to known vein-type Pb-Zn-Cu ores. Accordingly, a total of 21 water samples were collected from natural springs in the Köprücük, Çolaki, Kabakçilar and Ekinli areas where ore-bearing rocks are widely exposed. Stream-sediment samples were taken from the Kurt, Kizilda? and Karacalar and Billurik streams, and a total of 57 samples were sieved to three different size fractions (-80 + 140, -140 + 200 and -200 mesh) and analyzed by ICP-MS and IE methods. The concentrations of A1 Ba, Br, Fe, K, Mn, Na, Pb, SO4, U and F in the spring waters are higher than the values recommended as the maximum allowable levels in drinking waters. In the stream-sediment samples, the -200 mesh fraction yielded Mo, Pb, Zn, As, U and Ca contents higher than the world average crustal composition; moreover, metal contents were found to be generally elevated in this stream-sediment size fraction. As values, in particular, are several times higher than the mean values for granitic rocks of the region. In correlation coefficient studies of the spring waters, it was observed that the REE are inversely related to pH and significantly positively related to SO4, Fe and Al. Consequently, it is concluded that the concentrations of several major and minor elements and REE in the spring waters, and the distribution of elements in the different size fractions of the stream sediments, can be utilized both in geochemical prospecting and in identifying high risk areas for metal pollution. Copyright © TÜBITAK.
Keywords: Drainage geochemistry; Elazi?; REE; Spring water; Stream sediments; Turkey